The Analysis of the Roles of Muraqabah and Muhasabah as Internal Hisbah Instruments to Enhance Sharia Compliance in Islamic Bussiness - Dewi Mutmainnah (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
The research aims to explore the role of muraqabah and muhasabah as internal hisbah instruments in ensuring the consistency of Sharia compliance among business practitioners in conducting their business activities. This qualitative research utilizes a descriptive-analytical approach to examine how muraqabah and muhasabah play an important role as internal hisbah instruments in ensuring consistent Sharia compliance for modern business actors. The data, obtained from various books and journals, is collected, processed, and analyzed to derive conclussions regarding the roles of muraqabah and muhasabah as internal hisbah instruments to enhance Sharia compliance in Islamic bussiness. Muraqabah, as a form of supervision and monitoring, encourages continuous awareness among business people to comply with Sharia principles in making business decisions.  In this case, business people must understand, believe, and be aware that every action they take is under the supervision of Allah SWT. Meanwhile, muhasabah, as an in-depth self-evaluation instrument, provides a basis for critical reflection on every decision and business action. This evaluation does not only involve acceptance and acknowledgment of mistakes but also efforts to find solutions and improvement strategies for the benefit of the future. Muraqabah and muhasabah establish a dynamic internal monitoring mechanism, facilitating the enhanced identification of potential Sharia violations and the pursuit of corrective solutions for further improvement to achieve al-falah.